Upconversion Nanoparticles-Encoded Hydrogel Microbeads-Based Multiplexed Protein Detection - Swati Shikha (Nano-Micro Letters, 2017)
Abstract Fluorescently encoded microbeads are in demand for multiplexed applications in different fields. Compared to organic dye-based commercially available Luminex’s xMAP technology, upconversion nanoparticles (UCNPs) are better alternatives due to their large anti-Stokes shift, photostability, nil background, and single wavelength excitation. Here, we developed a new multiplexed detection system using UCNPs for encoding poly(ethylene glycol) diacrylate (PEGDA) microbeads as well as for labeling reporter antibody. However, to prepare UCNPs-encoded microbeads, currently used swelling-based encapsulation leads to non-uniformity, which is undesirable for fluorescence-based multiplexing. Hence, we utilized droplet microfluidics to obtain encoded microbeads of uniform size, shape, and UCNPs distribution inside. Additionally, PEGDA microbeads lack functionality for probe antibodies conjugation on their surface. Methods to functionalize the surface of PEGDA microbeads (acrylic acid incorporation, polydopamine coating) reported thus far quench the fluorescence of UCNPs. Here, PEGDA microbeads surface was coated with silica followed by carboxyl modification without compromising the fluorescence intensity of UCNPs. In this study, droplet microfluidics-assisted UCNPs-encoded microbeads of uniform shape, size, and fluorescence were prepared. Multiple color codes were generated by mixing UCNPs emitting red and green colors at different ratios prior to encapsulation. UCNPs emitting blue color were used to label the reporter antibody. Probe antibodies were covalently immobilized on red UCNPs-encoded microbeads for specific capture of human serum albumin (HSA) as a model protein. The system was also demonstrated for multiplexed detection of both human C-reactive protein (hCRP) and HSA protein by immobilizing anti-hCRP antibodies on green UCNPs.